Pembuktian Pelanggaran Asas-Asas Umum Pemerintahan yang Baik (AAUPB) sebagai Dasar Gugatan di PTUN - Chandra, Febrian; Azri, Muhammad; Apriadi Bahri, Rizki; Ananda, Tiara (PT. Meja Ilmiah Publikasi, 2025)
This study aims to analyze the standard of proof and the effectiveness of evidence in state administrative disputes based on violations of the General Principles of Good Governance (Asas-Asas Umum Pemerintahan yang Baik/AAUPB). The main focus is to answer how violations of abstract principles can be concretely proven in the proceedings of the State Administrative Court (PTUN), an area fraught with practical challenges for justice seekers. The research method used is normative juridical with statutory, case, and conceptual approaches. Primary and secondary legal materials were analyzed qualitatively to identify evidentiary practices in jurisprudence. The results show that the standard of proof for AAUPB violations is flexible (vrij bewijs), depending on the judge's conviction supported by at least two valid pieces of evidence. Effective proof cannot rely on a single type of evidence but on a synergistic combination of written documents to trace the process, expert testimony to translate abstract norms, and witness testimony to reveal procedural facts. The impact of this research is the provision of a strategic framework for legal practitioners in formulating lawsuits and offering a basis for the development of judicial guidelines to enhance decisional consistency.